Multiple FDG-Avid Dermatofibromas Mimicking Cutaneous Metastasis: A Case Report Highlighting a Diagnostic Pitfall in Dermatology - Chiou, Allison; Maher, Eamonn (Case reports in dermatology, 2025)
Dermatofibromas are benign skin tumors that are typically diagnosed clinically without the need for biopsy. While they are not commonly associated with PET imaging findings, they have been occasionally reported to exhibit FDG uptake in radiology literature. However, this remains significantly underrecognized by many dermatologists. We describe a 42-year-old woman with a history of HER2-positive breast cancer who underwent PET-CT for surveillance. Multiple FDG-avid nodules were noted and initially interpreted as possible cutaneous metastases. Dermatologic evaluation revealed longstanding, stable papules consistent with dermatofibromas. Biopsy was deferred due to classic features and diagnostic certainty. Dermatofibromas can appear hypermetabolic on PET imaging due to histiocytic and inflammatory cell activity. Awareness of this pitfall is important for dermatologists involved in the care of oncology patients, as recognition may prevent unnecessary biopsies, oncologic escalation, and patient anxiety.